2022
DOI: 10.1155/2022/6176043
|View full text |Cite
|
Sign up to set email alerts
|

KRT17 Accelerates Cell Proliferative and Invasive Potential of Laryngeal Squamous Cell Carcinoma (LSCC) through Regulating AKT/mTOR and Wnt/β-Catenin Pathways

Abstract: Background. Laryngeal squamous cell carcinoma (LSCC) is a prevalent malignant tumor of the head and neck with a dismal prognosis. Keratin17 (KRT17) has been proven to serve as an oncogene in various cancers, but it has never been explored in LSCC. We proposed to assess the impact and possible mechanisms of KRT17 in the development of LSCC. Methods. Quantitative reverse transcription-PCR (qRT-PCR) was utilized to examine the mRNA levels. The Kaplan–Meier method was used to calculate the relationship between KRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In HPV-associated cancers, seven (12.5%) studies investigated the prognostic role of K17 in HNSCC [24,[38][39][40][41][42]52] and three (5.4%) studies in cervical SCC [22,34,53]. One study (1.8%) in HNSCC investigated both the prognostic and predictive role [15].…”
Section: Prognostic Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In HPV-associated cancers, seven (12.5%) studies investigated the prognostic role of K17 in HNSCC [24,[38][39][40][41][42]52] and three (5.4%) studies in cervical SCC [22,34,53]. One study (1.8%) in HNSCC investigated both the prognostic and predictive role [15].…”
Section: Prognostic Significancementioning
confidence: 99%
“…The details of biomarker assessment methodologies are presented in Supplemental Table S2. Studies investigating K17 at the transcriptome level (n = 24) have found K17 to hold negative prognostic value in most cancer entities (endometrial [30,71], esophageal [57], gastric [72], HNSCC [38,42,52], lung cancer [73,74], melanoma [75,76], pancreatic adenocarcinoma [50,51], and renal cell carcinoma [77]). In TNBC, a negative correlation between K17 RNA expression and outcome was found only in a subgroup of patients with invasive ductal carcinoma with large tumors and advanced stage [29].…”
Section: Prognostic Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of KRT17 regulating tumor progression is tissue specific [18,19]. For instance, KRT17 enhances the proliferation of oral cancer by up-regulating Akt/mTOR signal pathway and suppresses the content of cleaved-caspase-3 to strengthen its function [20]. Tissue-specific cytokine polarization can be induced by low expression of KRT17 in cervical cancer and it is necessary to recruit effector immune cells to vulnerable cervical epithelial cells to prevent the growth of cancer [21].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of KRT17 regulating tumor progression is tissue speci c [18,19]. For instance, KRT17 enhances the proliferation of oral cancer by up-regulating Akt/mTOR signal pathway and suppresses the content of cleaved-caspase-3 to strengthen its function [20]. Tissue-speci c cytokine polarization can be induced by low expression of KRT17 in cervical cancer and it is necessary to recruit effector immune cells to vulnerable cervical epithelial cells to prevent the growth of cancer [21].…”
Section: Introductionmentioning
confidence: 99%